Development and psychometric evaluation of a theory of planned behavior model-based instrument for evaluation of determinants of oral health behaviors in mothers of children younger than six years in Iraq - Rusul Abdulameer Hadi Al-Sarray; Ahmadreza Shamshiri; Muhammad Alzubidi; Mahdia Gholami; Simin Z. Mohebbi (BMC Oral Health)
Abstract Background The theory of planned behavior (TPB) is one of the most commonly used theories to explain oral health behaviors. To gain a deeper understanding of the determinants of oral health behaviors, we aimed to design and evaluate the psychometrics of a theory of planned behavior model-based instrument for assessing the determinants of oral health behaviors in mothers of children younger than six years in Iraq. Methods Questionnaires and guidelines related to the topic were searched in 2023, and the appropriate items based on the domains of the TPB model were extracted. The items were revised and completed to develop the initial version of the instruments. Face validity and content validity of the instrument were assessed. The content validity index (CVI) and content validity ratio (CVR) were calculated subsequently. The construct validity was examined by confirmatory factor analysis (CFA). Cronbach’s alpha, intra-class correlation coefficient (ICC), and percentage of agreement were employed to check the tool’s internal consistency and reproducibility reliability. The data were analyzed using SPSS version 25 and Amos software. Results The questionnaire had adequate content validity (CVR ≥ 0.75, CVI ≥ 0.75). The percentage of agreement, Kappa, and ICC coefficients were 57.1–95.3%, 0.52–0.89, and 0.43–0.90, respectively. The p-value for ICC was significant in all cases (p < 0.001). For the internal stability of the tool to keep Cronbach’s alpha values > 0.7 for all domains, we had to omit three questions from attitude, one from subjective norms, and one from perceived behavioral control. In terms of construct validity, the results were as follows: the Goodness of Fit Index (GFI) was 0.942, the Comparative Fit Index (CFI) was 0.900, the Adjusted Goodness of Fit Index (AGFI) was 0.921, and the Root Mean Square Error of Approximation (RMSEA) was 0.046. These values indicate that the instrument demonstrates appropriate construct validity based on the TPB. Conclusion The psychometric evaluation of the designed instrument showed that it was a valid and reliable tool in Arabic-speaking countries for determining child-related oral health behaviors in mothers of children under six years old.